• $(A^*)^*=|A|^{n-2}A(A为可逆方阵)$。

$$A^*(A^*)^*=|A^*|E$$

$$\Rightarrow (A^*)^{-1}A^*(A^*)^*=(A^*)^{-1}|A^*|E$$

$$\Rightarrow (A^*)^*=(A^*)^{-1}|A^*|E\tag{1}$$

$$AA^*=|A|E$$

$$\Rightarrow|AA^*|=||A|E|$$

$$\Rightarrow|A||A^*|=|A|^n$$

$$\Rightarrow|A^*|=|A|^{n-1}\tag{2}$$

$$A^*=|A|A^{-1}$$

$$\Rightarrow (A^*)^{-1}=(|A|A^{-1})^{-1}$$

$$\Rightarrow (A^*)^{-1}=|A|^{-1}A\tag{3}$$

$$(1),(2),(3)\Rightarrow (A^*)^*=|A|^{n-2}A\tag{4}$$

  • $(kA)^*=k^{n-1}A^*(A为可逆方阵)$

$$(kA)(kA)^*=|kA|E$$

$$=|kA|(kA)^{-1}$$

$$=k^n|A|k^{-1}A^{-1}$$

$$=k^{n-1}|A|A^{-1}$$

$$=k^{n-1}A^*\tag{5}$$

  • $(A^*)^{-1}=(A^{-1})^*(A为可逆方阵)$

$$(A^*)^{-1}=(|A|A^{-1})^{-1}$$

$$=|A|^{-1}A$$

$$=|A|^{1-n}|A|^{n-2}A\tag{6}$$

$$(4),(5),(6)\Rightarrow (A^*)^{-1}=|A|^{1-n}(A^*)^*$$

$$=(|A|^{-1})^{n-1}(A^*)^*$$

$$=(|A|^{-1}A^*)^*$$

$$=(A^{-1})^*$$

Last modification:January 28th, 2021 at 11:11 pm
博客维护不易,如果你觉得我的文章有用,请随意赞赏